(untitled) (Symposium on Natural and Applied Sciences, 2026)
This article provides a systematic analysis of the stages of economic development of the Koson district, one of the largest regions of the Kashkadarya region, during the years of independence. The article highlights the agrarian reforms in the district, the transition from cotton monopoly to diversified agriculture, the growth of industrial potential, and the stages of formation of small business and private entrepreneurship based on archival data and statistical indicators. Also, structural changes and the dynamics of economic growth implemented in the district are described in the form of textual analysis over the years.